Case report: Aggressive progression of acute heart failure due to juvenile tuberculosis-associated Takayasu arteritis with aortic stenosis and thrombosis - Xuan, Wenjie; Wang, Zhaoling; Lin, Jinjing; Zou, Lixia; Xu, Xisheng; Yang, Xinghui; Xu, Yiping; Zhang, Yan; Zheng, Qi; Xu, Xuefeng; Lu, Meiping (Frontiers in Cardiovascular Medicine, 2023)
Background: Takayasu arteritis (TA) is a chronic and granulomatous vasculitis with unknown pathophysiology. Tuberculosis (TB) infection-associated TA in childhood is rare. We report a case of TA associated with TB in a Chinese boy, who presented with aggressive acute heart failure (AHF), pulmonary hypertension (PH), thrombosis and seizure which eventually led to death. Case presentation: A 10-year-old boy who developed a cough with chest tightness, shortness of breath, hemoptysis with lower (40%) left ventricular ejection fraction, high NT- proBNP (19052 pg/mL) and PH (75 mmHg) was hospitalized at PICU of our hospital. Calcified left hilar lymph nodes, occlusion of proximal left subclavian artery, stenosis of descending aorta and upper abdominal aorta were found. PPD and T-SPOT test revealed strong positive. His condition did not improve after he accepted milrinone, diuretics, antihypertensive agents, anti-TB medications and intravenous methylprednisolone pulse (IVMP) followed by 1 mg/kg/d of prednisone. Intravenous tocilizumab was administered for 3 doses, and he was significantly relieved and discharged on day 60. However, one week later, he was hospitalized again because of worse heart failure, and CTA showed complete occlusion of the descending aorta with large thrombosis. He was failed to any anti-inflammatory treatment including IVMP, another dose of tocilizumab then replaced by 2 doses of infliximab. He had a seizure on day 99. He accepted balloon angioplasty and catheter-directed thrombolysis started on day 127. Unfortunately, the child's heart function continued to deteriorate four days after surgery, the family gave up treatment, and the patient died on day 133. Conclusion:TB infection may involve in pathogenesis of juvenile TA. It had a poor prognosis and limited efficacy of biologics, thrombolysis in aggressive AHF due to severe aortic stenosis and thrombosis. Surgery is controversial in pediatric TA. Keywords: Juvenile, Takayasu arteritis, Acute heart failure, Pulmonary hypertension,Thrombosis, Surgery